Outpatient management of Yenching Traditional Chinese Medicine Nursing Clinics (燕京中医护理系列门诊管理实践) - ZHAO Guomin (赵国敏); HE Hong (何红); HAO Li (郝丽) (中西医结合护理)
Supported by the constructions of key medical and nursing disciplines in Beijing Hospital of Traditional Chinese Medicine and Gui Meifen Traditional Chinese Medicine Nursing Inheritance Work, the Yenching Traditional Chinese Medicine Nursing Clinics have been established, which provide a variety of Traditional Chinese Medicine nursing service for skin and external diseases, breast disorders, stoma, skin, intravenous therapy and so on. The construction of Yenching Traditional Chinese Medicine Nursing Clinics aims at spreading and inheriting Traditional Chinese Medicine culture, promoting the talent cultivation and disciplinary development, and providing a continuous, comprehensive, individualized and specialized nursing service. (首都医科大学附属北京中医医院护理部依托医疗、护理重点专科和“桂梅芬中医护理传承工作室”平台, 建立了涵盖疮疡、乳腺、造口、皮肤、静疗专业的“燕京系列护理门诊”。通过护理门诊建设, 传承中医护理理论和特色护理技术, 促进中医护理人才培养、推动护理学科发展, 为患者提供连续、全面、全程、个性化、安全的专科护理服务。)